Moody choice - Paola Manzini; Marco Mariotti (Institute for the Study of Labor (IZA), 2010)
If choices depend on the decision maker's mood, is the attempt to derive any consistency in choice doomed? In this paper we argue that, even with full unpredictability of mood, the way choices from a menu relate to choices from another menu exhibits some structure. We present two alternative models of 'moody choice' and show that, in either of them, not all choice patterns are possible. Indeed, we characterise both models in terms of consistency requirements of the observed choice data.
Keywords: D01; 330; Bounded rationality; procedural rationality; utility maximization; choice behavior; Entscheidung; Emotion; Beschränkte Rationalität; Eigeninteresse; Präferenztheorie; Theorie